Government Paradiplomacy in Proposing Penyengat Island to UNESCO as a World Cultural Heritage - Vira Anggelina Putri; Ady Muzwardi; Rizqi Apriani Putri (Journal of Maritime Policy Science, 2025)
The cultural wealth of Indonesia, particularly from border regions such as the Kepulauan Riau, is increasingly threatened by external claims and lack of international recognition. One prominent case involves Penyengat Island, a significant historical and cultural site in Tanjungpinang, rich in Malay heritage and once a center of the Riau-Lingga Sultanate. Recognizing the island’s cultural and historical value, the Government of Kepulauan Riau Province has initiated efforts to nominate Penyengat Island as a UNESCO World Cultural Heritage Site. This study aims to examine the paradiplomatic strategies employed by the local government in this international cultural diplomacy effort. Using a qualitative descriptive approach, the research collects data through interviews with key officials from the Tanjungpinang Department of Culture and Tourism, field observations, and document analysis. The findings reveal that the local government has undertaken significant initiatives, including the revitalization of historical sites, the preparation of comprehensive documentation and cultural dossiers, and the lobbying of national institutions to support the nomination. The concept of paradiplomacy where sub-national governments engage in international relations proves central to these efforts. While challenges such as limited administrative authority and bureaucratic hurdles persist, the strategic collaboration with the central government and UNESCO-aligned bodies demonstrates the growing agency of local governments in global cultural advocacy. The study concludes that effective paradiplomacy can serve as a critical tool for promoting local heritage on the world stage, emphasizing the need for sustained intergovernmental cooperation and cultural diplomacy frameworks.